2011
DOI: 10.5491/shaw.2011.2.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Lymphohematopoietic Cancer Mortality and Morbidity of Workers in a Refinery/Petrochemical Complex in Korea

Abstract: ObjectivesThe purpose of this retrospective cohort study was to investigate the relationship between exposure of Korean workers to petrochemicals in the refinery/petrochemical industry and lymphohematopoietic cancers.MethodsThe cohort consisted of 8,866 male workers who had worked from the 1960s to 2007 at one refinery and six petrochemical companies located in a refinery/petrochemical complex in Korea that produce benzene or use benzene as a raw material. Standardized mortality ratios (SMRs) and standardized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 21 publications
0
21
0
1
Order By: Relevance
“…This is the first study to present this result with this understudied population. [2][3][4][5][6][7][8][9][10] Increased risk of oral and pharyngeal cancers has been reported for other occupational groups including: construction workers, machine workers, painters, plumbers, carpet installers, vehicle repair workers, textile workers, leather industry workers, pulp industry workers, wood workers, sugarcane farmers, and butchers. [18][19][20][21][22][23][24][25][26][27][28][29][30] Among the aforementioned study populations, a relatively strong association has been found among oral and pharyngeal cancers and construction workers and machine operators.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…This is the first study to present this result with this understudied population. [2][3][4][5][6][7][8][9][10] Increased risk of oral and pharyngeal cancers has been reported for other occupational groups including: construction workers, machine workers, painters, plumbers, carpet installers, vehicle repair workers, textile workers, leather industry workers, pulp industry workers, wood workers, sugarcane farmers, and butchers. [18][19][20][21][22][23][24][25][26][27][28][29][30] Among the aforementioned study populations, a relatively strong association has been found among oral and pharyngeal cancers and construction workers and machine operators.…”
Section: Discussionmentioning
confidence: 96%
“…However, in a previous cohort study examining the cancer risks of petrochemical plant employees at the same refinery/petrochemical complex, no significantly increased risk for lip, oral cavity, and pharynx cancer risk was observed compared to the general population. 4 This leads us to believe that there is the possibility of exposure to a carcinogen beyond salted fish. In particular, metal work, such as welding or working with cutting oil, has been reported to increase the risk of nasopharyngeal cancer.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Литературные данные говорят и о нарушении терморегуляции под влиянием углеводородов. Отмечается паде-ние температуры тела при действии бензина [22].…”
unclassified